2021
DOI: 10.7759/cureus.17314
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate Pulmonary Embolism Following Vertebroplasty

Abstract: Polymethylmethacrylate (PMMA) is a commonly used substrate in vertebroplasty procedures. Well-known for its dependable strength and relative lack of toxic side effects, PMMA administration is useful for the stabilization of vertebral bodies in the setting of common spinal pathologies such as osteoporosis. Unfortunately, as the popularity of vertebroplasty has increased, so has the incidence of a potentially lethal complication of the procedure, PMMA pulmonary embolism. Extravasation of PMMA from the vertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…8 However, the use of PMMA in vertebroplasty has some drawbacks such as poor osseointegration with host bone, non-degradable behavior, and low biocompatibility. [9][10][11] In addition, a high polymerization temperature of PMMA has been discovered, which can damage adjacent cells. [11][12][13] Furthermore, due to its higher mechanical strength and elastic modulus, PMMA alone is not an optimal choice for engineering cancellous bone tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, the use of PMMA in vertebroplasty has some drawbacks such as poor osseointegration with host bone, non-degradable behavior, and low biocompatibility. [9][10][11] In addition, a high polymerization temperature of PMMA has been discovered, which can damage adjacent cells. [11][12][13] Furthermore, due to its higher mechanical strength and elastic modulus, PMMA alone is not an optimal choice for engineering cancellous bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polymethylmethacrylate (PMMA) has emerged as an excellent biomaterial to use as a bone cement in vertebroplasty 8 . However, the use of PMMA in vertebroplasty has some drawbacks such as poor osseointegration with host bone, non‐degradable behavior, and low biocompatibility 9–11 . In addition, a high polymerization temperature of PMMA has been discovered, which can damage adjacent cells 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Most bone cement leaks are asymptomatic (2). In the past, several studies have reported serious complications of pulmonary embolism caused by bone cement leakage to the inferior vena cava (3). However, it is rare that bone cement leakage causes lesions in adjacent organs, and inexperienced doctors may overlook the association between these conditions and vertebroplasty.…”
Section: Introductionmentioning
confidence: 99%